Evading the “Entrepreneurial Blocks” through Entrepreneurial Marketing Education in Vocational High Schools in an Emerging Country - Haryanto, Jony Oktavian; Widyanto, Hanif Adinugroho; Suryanto, Hari; Santoso, Adhi Setyo (ASEAN Marketing Journal, 2022)
Entrepreneurial marketing education is considered an essential platform to stimulate successful entrepreneurs, especially for vocational high school (SMK) graduates in Indonesia, which has the highest open unemployment rate and mostly comes from low-income backgrounds. Hence, the researchers investigated why most SMK graduates, supposedly skilful, do not opt for entrepreneurship. This is an under-researched study that could carry enormous implications. The researchers interviewed participants from SMKs in Mataram, Indonesia, three entrepreneurship teachers and six students of entrepreneurship classes from grades 10 to 12. They referred to the extant literature as a basis for a proposed “Entrepreneurial Blocks” framework to explain the barriers and supporting factors for becoming an entrepreneur. Our findings show that entrepreneurial mindset, starting capital, challenges, risk aversion, and limited skills and resources were part of the entrepreneurial blocks. Conversely, working experience, desire for freedom, and the need for achievements were considered the factors to evade the entrepreneurial blocks for SMK graduates.